2005
DOI: 10.1029/2004jc002310
|View full text |Cite
|
Sign up to set email alerts
|

A modified law‐of‐the‐wall applied to oceanic bottom boundary layers

Abstract: [1] Near the bottom, the velocity profile in the bottom boundary layer over the continental shelf exhibits a characteristic law-of-the-wall that is consistent with local estimates of friction velocity from near-bottom turbulence measurements. Farther from the bottom, the velocity profile exhibits a deviation from the law-of-the-wall. Here the velocity gradient continues to decrease with height but at a rate greater than that predicted by the law-of-thewall with the local friction velocity. We argue that the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 19 publications
6
98
0
Order By: Relevance
“…This is probably due to the violation of assumptions underlying the law-of-the-wall parameterization (Li 1994;Smith and McLean 1977). In addition, the presence of stable stratification (e.g., Lien and Sanford 2004;Perlin et al 2005) and the details of bottom roughness and corresponding form drag (Li 1994;Sanford and Lien 1999;Edwards et al 2004) also contribute to the disparity. Lozovatsky et al (2008b) present further discussions on this issue with application to ECS shelf.…”
Section: Background Tidal Dynamics and Stratificationmentioning
confidence: 95%
See 1 more Smart Citation
“…This is probably due to the violation of assumptions underlying the law-of-the-wall parameterization (Li 1994;Smith and McLean 1977). In addition, the presence of stable stratification (e.g., Lien and Sanford 2004;Perlin et al 2005) and the details of bottom roughness and corresponding form drag (Li 1994;Sanford and Lien 1999;Edwards et al 2004) also contribute to the disparity. Lozovatsky et al (2008b) present further discussions on this issue with application to ECS shelf.…”
Section: Background Tidal Dynamics and Stratificationmentioning
confidence: 95%
“…It was found, however, that in the presence of weak stable stratification, velocity profile may exhibit a seemingly logarithmic structure, even though this log-layer may not support a constant vertical momentum flux, and u * so deduced can be much larger than the actual friction velocity. Specific modifications to u * obtained from shear profiles dU(ζ)/dζ have been suggested (e.g., Friedrichs and Wright 1997;Perlin et al 2005;Taylor and Sarkar 2008) to account for the influence of stratification. The u * deduced from the modified formulae was approximately half of its law-ofthe-wall-based counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that a tight logarithmic profile is not observed. Also, a two-fold log layer ('modified law of the wall'), as in Perlin et al (2005), is not observed here. These discrepancies with figure 5.…”
Section: Discussionmentioning
confidence: 89%
“…The 3-D simulations will also be equipped with virtual Eulerian ADVs spanning the lower 10% of the water column and virtual seafloor pressure sensors. Simulated dissipation rates combined with virtual ADV data will help assess the efficiency of proposed parameterizations of NLIW energy losses due to interactions with the seafloor (Perlin et al 2005) and the energetic impact of such losses in along-path energy transport by NLIWs (Moum et al 2007) as measured in the ONR-funded New Jersey Shallow Water 06 experiment on the New Jersey shelf. Furthermore, high-pass filtered virtual pressure sensor data can provide insight towards the signature of NLIW-induced turbulence in high-frequency seafloor pressure sensors (Moum and Nash 2007) compensated for hydrostatic pressure effects.…”
Section: Resultsmentioning
confidence: 99%